Development and evaluation of a training program for interpreters in the field of trauma-focused cognitive behavioral therapy - Müller, Lauritz Rudolf Floribert; Herold, Monja Lucia; Unterhitzenberger, Johanna; Rosner, Rita (Frontiers in Psychology, 2023)
Background: The treatment of traumatized refugee minors is often challenging be-cause of language barriers. International guidelines, therefore, recommend the use of language mediators. However, there is a scarcity of evaluated training programs that prepare language mediators to translate during psychotherapy developed specifically for this patient group, for instance trauma-focused cognitive behavioral therapy (TF-CBT). Methods: Based on an extensive literature review and in collaboration with an expert focus group, a one-day TF-CBT-specific online training program was developed for language mediators willing to work with minor refugees, and delivered on nine occasions between No-vember 2020 and June 2021. The participants answered pre- and post-training questions about trauma- and TF-CBT-related knowledge and attitudes relevant to therapy, as well as the per-ceived usefulness of the training. Bayesian estimation was used to determine pre-post chang-es. Results: A total of 129 participants speaking 35 different languages participated in the training program. Analyses revealed 95% highest density intervals not containing the null with respect to knowledge gain (effect size median 0.28) and change in treatment-appropriate atti-tudes (effect size median 0.31). The participants rated the training as useful. Conclusions: The TF-CBT-specific training course was successfully carried out. It was likely to disseminate both knowledge gains and a shift towards more treatment-appropriate attitudes. It was perceived as useful by the participants. Given the scarcity of evaluated train-ing programs for language mediators working with minor refugees, the results are promising. The limitations include the lack of both a control group and the verification of the results us-ing an external outcome measure.